The spatial dimension in the de-reconfiguration of the sexual division of labor: Examining the Madrid City of Care Plan - Porras Sánchez, Sara (Cuadernos de Relaciones Laborales, 2025)
This article proposes an approach to the study of the city that places at the center the structure of the Sexual Division of Labor (SDL) as the organizing backbone of urban space. From this perspective, it systematizes and analyzes one of the most ambitious initiatives in the field of local policies: the Madrid City of Care Government Plan (MCC) (2016–2019). This Plan was organically embedded as one of the strategic pillars of the Ahora Madrid government, being its first major action approved in the Plenary. The analysis is presented through a triangulation of methods, highlighting the symbolic–discursive dimension of the city, grounded in the notion of Gendered Spatial Order. The main conclusions suggest that the greatest resistance to implementing innovative public policies in this field lies in the symbolic order, challenging the possibility of imagining a spatial order not configured by the home/city divide. The difficulty in understanding and receiving the proposal of the “caring city” is reinforced by existing hegemonic imaginaries about urban coexistence and care.